Mutual Facilitation Among Invading Nuttall’s Waterweed and Quagga Mussels - Wegner, Benjamin; Kronsbein, Anna Lena; Gillefalk, Mikael; van de Weyer, Klaus; Köhler, Jan; Funke, Elisabeth; Monaghan, Michael T.; Hilt, Sabine (Frontiers in Plant Science, 2019)
Nuttall’s waterweed (Elodea nuttallii) is the most abundant invasive aquatic plant species in several European countries. Elodea populations often follow a boom-bust cycle, but the causes and consequences of this dynamics are yet unknown. We hypothesise that both boom and bust periods can be affected by dreissenid mussel invasions. While mutual facilitations between these invaders could explain their rapid parallel expansion, subsequent competition for space might occur. To test this hypothesis, we use data on temporal changes in the water quality and the abundance of E. nuttallii and the quagga mussel Dreissena r. bugensis in a temperate shallow lake. Lake Müggelsee (Germany) was turbid and devoid of submerged macrophytes for 20 years (1970-89), but re-colonisation with macrophytes started in 1990 upon reductions in nutrient loading. We mapped macrophyte abundance from 1999 and mussel abundance from 2011 onwards. E. nuttallii was first detected in 2011, spread rapidly, and was the most abundant macrophyte species by 2017. Native macrophyte species were not replaced, but spread more slowly, resulting in an overall increase in macrophyte coverage to 25% of the lake surface. The increased abundance of E. nuttallii was paralleled by increasing water clarity and decreasing total phosphorus concentrations in the water. These changes were attributed to a rapid invasion by quagga mussels in 2012. In 2017, they covered about one-third of the lake area, with mean abundances of 3,600 mussels m-², filtering up to twice the lake’s volume every day. The increasing light availability in deeper littoral areas supported the rapid spread of waterweed, while in turn waterweed provided surface for mussel colonisation. Quantities of dreissenid mussels and E. nuttallii measured at 24 locations were significantly correlated in 2016, and yearly means of E. nuttallii quantities increased with increasing mean dreissenid mussel quantities between 2011 and 2018. In 2018, both E. nuttallii and dreissenid abundances declined. These data imply that invasive waterweed and quagga mussels initially facilitated their establishment, supporting the invasional meltdown hypothesis, while subsequently competition for space may have occurred. Such temporal changes in invasive species interaction might contribute to the boom-bust dynamics that have been observed in Elodea populations.